Indications and Outcomes of Medical Intensive Care Admissions in a Nigerian Tertiary Hospital - Akinjola OE; Olateju SO; Idowu AO; Aaron OI; Adetoye AO; Ogunmodede AF; Andero V; Komolafe MA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Background: The demand for intensive care is rising in many developing countries with specialties requiring specialized intensive care services. Medical conditions constitute a substantial proportion of demands for intensive care. Objectives: To determine the patients' characteristics and outcomes of medical indications for intensive care unit (ICU) admissions in a Nigerian tertiary hospital. Methods: A retrospective descriptive study was conducted at the Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Southwest Nigeria. The data of all patients aged 16 years and above managed from 2010 to 2019 were extracted from the general ICU admissions book. The age, sex, indication for admission, need for mechanical ventilation, length of stay in the ICU and outcome of care were retrieved for analysis. Results: There were 255 patients with medical conditions, constituting 12.6% of all (3,213) ICU admissions during the study period. The male-to-female ratio was 1.3:1.0 and the age range was 16 to 89 years. The most common indication for admission was neurological illnesses (56.7%). Stroke accounted for 40.4% of all medical ICU admissions. The mean length of ICU stay was 4.9±5.95 days. A larger proportion of patients (75.0%) who had mechanical ventilation died compared to 25.0% who survived (p = 0.001). Conclusion: Neurological disorders, especially stroke, were the most common indications for ICU admission. Many medical conditions had high mortality rates and outcomes were notably poor for mechanically ventilated patients.